Virtual R&D teams: a potential growth of education-industry collaboration - Ale Ebrahim, N.; Ahmed, S.; Abdul Rashid, S.H.; Taha, Zahari (2010)
In this paper, we present our more than two years research experiences on virtual R&D teams in small and medium-sized enterprises (SMEs) and draws conclusions, giving special attention to the structure of virtual teams required to support education-industry collaboration. We report the relevant results of an online survey study. The online questionnaire was emailed by using a simple random sampling method to 947 manufacturing SMEs. The findings of this study show that SMEs in Malaysia and Iran are willing to use virtual teams for collaboration and the platform for industry-education collaboration is ready and distance between team members or differences in time zones, are not barriers to industry-education collaborations.